Penyisipan Gen Inhibitor α-amilase pada Plasmid Biner pCambia 1301 - Listanto, Edy; Sutrisno, Sutrisno; Pardal, Saptowo J.; Herman, M. (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2005)
The experiment was conducted at the Molecular Biology Laboratory of the Indonesian Center for Agricultural Biotechnology and Genetic Resources Research and Development, Bogor. The objective was to construct -ai gene on a binary plasmid pCambia 1301. This experiment was carried out using construction method by ligation process between fragments of α-ai gene from pTA3 plasmid and pCambia 1301 on HindIII site. The result of ligant transformation into E. coli DH5α was 182 surviving colonies on YEP medium containing kanamycin. DNA samples were obtained from 60 randomly selected colonies. The restriction pattern was tested by digesting each DNA sample using HindIII showed colonies containing two fragments expected of sizes wich are 11.837 and 4.887 kb. Two colonies are predicted containing of α-ai gene on its the binary plasmid. Advanced tests using restriction enzymes BamHI and XbaI showed two directions (right and left) of α-ai gene. The right direction was shown by pCambia-α-ai1 from colony number 43. This plasmid showed expected fragments of sizes 13.485 and 3.219 kb when digested with BamHI and two fragments of sizes 15.421 and 1.303 kb when digested with XbaI. The left direction was shown pCambia-α-ai2 from colony number 58. This plasmid also demon-strated expected fragments of sizes 15.026 and 1.698 kb when digested with BamHI and two fragments of sizes 13.082 and 3.642 kb when digested with XbaI. Both pCambia-α-ai1 and pCambia-α-ai2 were transformed into A. tumefaciens LBA4404.